answersLogoWhite

0


Best Answer

That factors to (2c + 3)(3c + 2)

User Avatar

Wiki User

โˆ™ 2012-05-15 23:06:33
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

๐Ÿ““
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What is 6c squared plus 13c plus 6?
Write your answer...
Submit
Related questions

What is the answer to 13c-7 plus c-d?

6


What is 6 squared plus 9 squared?

6 squared plus 9 squared is equal to 117.


What is 9 b plus 6 c plus 4 b?

13b+6c


What is 6 squared plus three?

6 squared is 36. 36 plus 3 is 39


What is 6 squared plus 11 squared?

It is: 36 plus 121 = 157


What is 6 squared plus 2 squared?

40


What is 6 squared plus 3?

6 squared plus 3 is equal to 39.


13c-7 plus c-d?

6


Where is the center of the circle given by the equation x plus 4 squared plus y plus 6 squared equals 49?

(-4,-6)


How does the entropy change in the reaction 2C3H6 902 -- 6C)2 plus 6 H2O?

The entropy increases:)


C-6 C plus 7?

C - 6C + 7 = -5C + 7


What is the value of 6 squared plus 8 squared?

102 or 100


What is 6 plus the result of x squared plus 2 divided by 1?

8 + X SQUARED


What is 16a plus 3b-c-5a plus 3b plus 7c plus a equals?

12a + 6b + 6c = 6(2a + b + c)


What is 6 squared plus 8 squared?

100 is.


What is 5 squared plus 6?

52 + 6 = 31


How would you write the equation for one cow and one horse when one farmer buy 6 cows and 7 horses for 2500 and the other 13 cows and 1 horse for 2310?

6c + 7h = 2500 . . . . . (A) 13c + h = 2310 . . . . . (B) By (B), h = 2310 - 13c Substituting this value in (A) gives 6c + 7*(2310 - 13c) = 2500 or 6c + 16170 - 91c = 2500 that is, 85c = 13670 so that c = 16014/17 Then h = 2310 - 13c gives h = 2310 - 2090156/221 = 21965/221. The answers suggest that there is an error in the number of animals bought.


What is the solution to x squared equals x plus 6?

X squared = x+6 6+x=x squared X=6


What is 6 plus 3 squared?

15.


Factorise m squared plus 7m plus 6?

(m + 6)(m + 1)


How do you solve or factor 5x squared plus 33x plus 18?

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5


What is 3 squared - 2 squared plus 6 squared?

9 - 4 =5, 5+36= 41


How do you factor x squared minus 12 x plus 36?

x squared minus 12 x plus 36 = (x - 6)(x - 6)


How do you simplify 6 x squared minus 2x plus 5 plus 2 x squared minus 7x - 11?

No


How do you factor 6X squared plus 12X plus 6?

6(x + 1)(x + 1)